QUANTIFYING LIFE STYLE IMPACT ON LIFESPAN - Lorenzini, Antonello (Annales Kinesiologiae, 2012)
A healthy diet, physical activity and avoiding dangerous habits such as smoking are effective ways of increasing health and lifespan. Although a significant portion of the world’s population still suffers from malnutrition, especially children, the most common cause of death in the world today is non-communicable diseases. Overweight and obesity significantly increase the relative risk for the most relevant non communicable diseases: cardiovascular disease, type II diabetes and some cancers. Childhood overweight also seems to increase the likelihood of disease in adulthood through epigenetic mechanisms. This worrisome trend now termed “globesity” will deeply impact society unless preventive strategies are put into effect. Researchers of the basic biology of aging have clearly established that animals with short lifespans live longer when their diet is calorie restricted. Although similar experiments carried on rhesus monkeys, a longer-lived species more closely related to humans, yielded mixed results, overall the available scientific data suggest keeping the body mass index in the “normal” range increases the chances of living a longer, healthier life. This can be successfully achieved both by maintaining a healthy diet and by engaging in physical activity. In this review we will try to quantify the relative impact of life style choices on lifespan.